Transcriptome Analysis Reveals Key miRNA–mRNA Pathways in Ovarian Tissues of Yunshang Black Goats With Different Kidding Numbers - Liu, Yufang; Zhou, Zuyang; Guo, Siwu; Li, Kunyu; Wang, Peng; Fan, Yekai; He, Xiaoyun; Jiang, Yanting; Lan, Rong; Chen, Shuangzhao; Dai, Shenghong; Hong, Qionghua; et al. (Frontiers in Endocrinology, 2022)
The granulosa cell (GC) is the basic functional unit of follicles, and it is important for promoting follicle growth and sex hormones, as well as growth factor secretion in the process of reproduction. A variety of factors influence granulocyte proliferation, yet there are still many gaps to be filled in target and non-coding RNA regulation. In our study, the differentially expressed (DE) mRNAs and miRNAs were detected by using RNA-seq, and we constructed a mRNA–miRNA network related to goat prolificacy. Then, the goat primary GCs were isolated from the follicle for the function validation of candidate genes and their regulator miRNAs. A total of 2,968 DE mRNAs and 99 DE miRNAs were identified in the high- and low-prolificacy goat by RNA-seq, of which there were 1,553 upregulated and 1,415 downregulated mRNAs, and 80 upregulated and 19 downregulated miRNAs, respectively. JAK3 was identified as highly expressed in the low-prolificacy goats (3 times higher than high-prolificacy goats), and the integrated analysis showed that chi-miR-493-3p was a potential regulator of JAK3. The analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that JAK3 was involved in the PI3K-Akt signaling pathway, the Jak-STAT signaling pathway, and signaling pathways regulating pluripotency of stem cells. In particular, the PI3K-Akt signaling pathway was a typical pathway for cell proliferation, differentiation, apoptosis, and migration. We found that the chi-miR-493-3p targets JAK3 directly via RT-qPCR, dual fluorescence assays, and Western blot. Furthermore, the expression of JAK3 was significantly decreased by the chi-miR-493-3p mimic and increased by the chi-miR-493-3p inhibitor. The CCK-8 assay showed that overexpression of JAK3 promoted cell proliferation, while inhibiting JAK3 had the opposite effect. The expression of cell proliferation markers CDK4 and cyclin D2 also showed the same results. Moreover, the enzyme-linked immunosorbent assay showed that steroid hormones E2 and PROG were increased by overexpressing JAK3 and decreased by inhibiting JAK3. Therefore, our results identified a chi-miR-439-3p-JAK3 regulatory pathway, which provided a new insight into the GC proliferation and prolificacy of goat.